The underestimated role of plant root nitric oxide emission under low-oxygen stress - Welle, Marcel; Niether, Wiebke; Stöhr, Christine (Frontiers in Plant Science, 2024)
The biotic release of nitric oxide (NO), a greenhouse gas, into the atmosphere contributes to climate change. In plants, NO plays a significant role in metabolic and signaling processes. However, little attention has been paid to the plant-borne portion of the global NO emissions. Owing to the growing significance of global flooding events caused by climate change, the extent of plant NO emissions has been assessed under low-oxygen conditions for the roots of intact plants. Each examined plant species (tomato, tobacco, and barley) exhibited NO emission in a highly oxygen-dependent manner. The transfer of data obtained under laboratory conditions to the global area of farm land has been used to estimate possible plant NO contribution to greenhouse gas budgets. Plant-derived and stress-induced NO emissions were estimated to account for equivalent of 1 to 9% of global annual NO emissions from agricultural land. Because several stressors induce NO formation in plants, the actual impact may be even higher.